Maternal Factors in Managing Seizures in Children - Dwiyanti Purbasari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Febrile seizures are medical emergencies commonly occurring in children aged 6 months to 5 years that require immediate and appropriate response. Maternal knowledge plays a critical role in managing these events to prevent complications.Objective : This study aims to examine the relationship between maternal knowledge, education, occupation, and age with the management of febrile seizures in children at Mitra Plumbon Hospital. A quantitative research design with a cross-sectional approach was used. A total of 84 mothers whose children experienced febrile seizures were selected through total sampling. A validated structured questionnaire was used as the instrument. The questionnaire underwent validity and reliability testing on a sample of 10 mothers to ensure its appropriateness for the study. Data were analyzed using the Spearman Rank test and ordinal regression.Result : The results showed that 45.2% of mothers had good knowledge and 47.6% demonstrated appropriate seizure management. Significant relationships were found between knowledge (r = 0.567; p < 0.001) and education (r = 0.287; p = 0.008) with seizure management. Age and occupation showed no significant correlation.Conclusion : It is concluded that maternal knowledge and education significantly influence the proper management of febrile seizures. Continuous health education for mothers is essential to improve emergency handling of febrile seizures at home.